Utilizing event marketing techniques in banking activities - Olga Petrykiva; Kristina Hordiienko (Фінансово-кредитні системи: перспективи розвитку., 2023)
clientele. Banking marketing, with its unique attributes, stands as a distinctive domain within the broader spectrum of marketing. In an era where banks primarily offer uniform services, competition among them has intensified substantially, necessitating a shift towards maximum customer-centricity and the application of marketing concepts. This research aims to investigate the theoretical and methodological underpinnings and formulate practical recommendations for enhancing the marketing support of banks, facilitating effective functioning, and establishing a diagnostic framework for assessing the utilization of marketing tools. The core tasks include a comprehensive examination and synthesis of the theoretical foundations of event marketing as a banking marketing instrument in the context of globalization and an analysis of the marketing activities of PJSC "PrivatBank" with subsequent recommendations for refining the management of its event marketing endeavors.